KAJIAN PENDUGAAN LETAK AKUMULASI AIR LINDI DENGAN METODE MAPPING RESISTIVITAS KONFIGURASI WENNER ( STUDI KASUS DI TPA PAKUSARI KAB. JEMBER ) - Rivan Indra Pratama; Noor Salim; Rusdiana Setyningtyas (HEXAGON, 2020)
The Pakusari Jember TPA uses the Open Dumping system, so that this system will cause groundwater and environmental pollution, one of which is through leachate. The research was conducted using geoelectricity with the Mapping Resistivity method, with 3 passes and a length of 130 m each, with a resistance value between 0.393 - 8.44 Ώm which is thought to be a rock layer filled with leachate. The connection between paths 1, 2 and 3 produces a color image, it shows that the intersection that occurs at the point of intersection is thought to be that the rock layers are in the form of clay and sand with a red image and upload. The cutting line aims to determine the relationship between line 1 and other lines as well as the location around the study and to determine the direction of movement of leachate distribution. The distribution of leachate in TPA Pakusari Jember, there are 7 points indicating the presence of leachate from the color image